Collective Memory and Identity Issues in Post-Soviet Belarus: Soft-Belarusisation and the Kastus’ Kalinoŭski Myth - Daria Cusitcaia; Ilaria Zaggia (eSamizdat, 2021)
The article aims to explore post-Soviet transition in Belarus with a focus on issues of identity, language, and collective memory, providing original insights to interpret the events of 2020. The reconstruction of the debate on identity models in Belarus constitutes the basis of the article, briefly covering the period from the early 1990s up to recent times. It is argued that, after 2014, the so-called Soft-Belarusisation highlighted some changes taking place in Belarusian society, manifested through civic initiatives and the shift in the government’s narrative. These will also be visible in the case study of the contested hero Kastus’ Kalinoŭski whose symbolic meaning has been reshaped in the memories of Belarusians after the 2020 protests. It is concluded that Soft-Belarusisation can be considered as a process of transition from an identity that still features many Soviet elements towards an identity under redefinition, which also incorporates elements from alternative models of national identity.